Methods of Increasing the Effectiveness of Training of Athletes Engaged in Primary Training Groups (Texas Journal of Multidisciplinary Studies, 2022)
The article gives an idea of the special tools and standards used in improving the effectiveness of training of 11-12-year-old students engaged in school athletics clubs. The also giving practical recommendations regarding the development of endurance of young athletes.